The purity of blood privilege for honours and positions. The Spanish Crown and the Ximenes de Aragão family. - López-Salazar, Ana Isabel (2016)
The case of the Ximenes family allows us to understand the different mechanisms used by the Portuguese New Christians to move upward in society; it also provides us with an example we can use as a basis for analyzing the different identities and tensions that existed within the Portuguese converso minority.